1994
DOI: 10.1159/000196319
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the Lung

Abstract: We describe a case of carcinosarcoma of the lung in a 60-year-old female who was admitted with complaints of productive cough and an abnormal shadow in the chest X-ray. Sputum cytology showed both squamous cell carcinoma and adenocarcinoma cells. Malignant nonepithelial cells were identified in the needle biopsy specimen. Right middle and lower lobectomy was performed to reveal a carcinosarcoma by microscopic and immunohistochemical examination. This case was histologically unusual because it presented multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Similarly, in 67% of our cases, the epithelioid component was squamous cell carcinoma, and it was adenocarcinoma in 33%. The sarcomatous component involves poorly differentiated osteosarcoma, chondrosarcoma, or rhabdomyosarcoma [5, 7, 8]. In our cases, osteosarcoma, chondrosarcoma, and spindle cell carcinoma were mostly seen in the sarcomatous component.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Similarly, in 67% of our cases, the epithelioid component was squamous cell carcinoma, and it was adenocarcinoma in 33%. The sarcomatous component involves poorly differentiated osteosarcoma, chondrosarcoma, or rhabdomyosarcoma [5, 7, 8]. In our cases, osteosarcoma, chondrosarcoma, and spindle cell carcinoma were mostly seen in the sarcomatous component.…”
Section: Discussionmentioning
confidence: 75%
“…The most common epithelial component is squamous cell carcinoma. Takeda et al reported a rate of 69% for squamous cell carcinoma, 24% for adenocarcinoma, and 6% for a combination of carcinomas [8]. Koss et al reported that the most frequent epithelial component was squamous cell carcinoma (46%), followed by adenocarcinomas (31%) and adenosquamous cell carcinoma (19%) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Debido a ello el diagnóstico histológico definitivo suele obtenerse por el examen microscópico de la pieza quirúrgica. Aunque el diagnóstico de carcinoma epidermoide es frecuente antes de la cirugía, existen casos de diagnóstico histológico certero antes de la cirugía descritos en la literatura bien por citología de esputo, punción transtorácica aspirativa con aguja fina o biopsia bronquial por fibrobroncoscopia (4,7,10).…”
Section: Discussionunclassified